Synthesis, Characterization of Novel Modified Reduced Graphene Oxide (RGO) Containing Heterocyclic Compounds - Fadhil, Hussein Ali; Samir, Ali H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In the present study, nanoderivatives were prepared for graphene sheets that were functionalized with triazoles, starting with the thermal treatment of a mixture of carbon disulfide and hydrazine hydrate, which afforded the thiacarbohydrazide (h5). Treatment of the latter with (salicylic and anthranilic) acid via a fuse heated in solid-state gave (h6) and (h7), respectively. Reaction of L-ascorbic acid with dry acetone in the presence of dry hydrogen chloride afforded the acetone (h1). Treatment of the latter with p-nitrobenzoyl chloride in pyridine yielded the ester (h2), which was dissolved in 65% acetic acid in absolute ethanol and yielded the glycol (h3). The reaction of the glycol with sodium periodate in distilled water at room temperature produced the aldehyde (h4), which was then condensed with compounds (h6, h7) in glacial acetic acid to produce (h8, h9) compounds. In addition, the (II, III, IV) compounds were used to exfoliate graphite (I), which contains graphite rods as both anode and cathode, electrolyte, and distilled water. Sodium bicarbonate is a powerful source for the formation of graphene oxide and graphite oxides with a variable acid (II). Graphene oxide’s interaction with hydrazine hydrate yielded (h3). The product of reduced graphene oxide (III) sonification with SoCl2 in dimethylformamide yielded (Acyl-chloride-functionalized Reduced graphene oxide) (IV). Reacting it with compounds (8h, 9h) in dry THF and Et3N produced compounds (h11, h12). The structures of the novel synthesized compounds were confirmed by physical properties and spectral analysis by FTIR spectroscopy, and some of them by 1H,13C-NMR spectra, X-ray diffraction, scanning electron microscope (SEM), and FASEM.